Success of Chain-Of-Command Oral Communication In A Manufacturing Management Group - Davis, Keith (Academy of Management Journal, 1968)
Oral chain-of-command communication in a manufacturing management group was surveyed using ecco analysis. Routine information was blocked by operating management, but production information was effectively communicated, it is suggested that in a manufacturing environment certain information is more appropriate for written communication than for oral communication, because oral communication in these instances requires uneconomic use of valuable management time.